(untitled) (GAIMS Journal of Medical Sciences, 2024)
Treacher Collins syndrome is an autosomal dominant genetic disorder that results from improper development of the first and second pharyngeal arches. Disruption in the formation and migration of neural crest cells leads to facial malformation. Face shows a convex profile with hypoplastic malar bones as well as mandibular hypoplasia. Eyes typically have antimongoloid slant often with lower lid coloboma. External ear is deformed and patients often suffer from conductive deafness. Respiratory distress is common due to hypoplastic facial bones. Though intelligence remains unaffected, such patients are susceptible to depression. Management of these patients require multidisciplinary approach to ensure a decent quality of life.